Comfort as an attentive presence in interpersonal professional practice - Mæhre, Kjersti Sunde; Halås, Catrine Torbjørnsen (Nordisk Tidsskrift for Helseforskning, 2022)
In this scientific essay, the significance of emotional support is made visible in interpersonal professional practices. The authors show, through two separate research projects in two different disciplines, the importance of having a sensory attentive presence in meetings with people who experience that life is threatened due to illness or other existential basic conditions. In the essay, it is the appearances of emotional support that we have paid attention to, and then through examples and stories from the research. In dialogue with the humanistic philosophy of practice, we make emotional support visible as significant in professionals’ meetings with the other and write an understanding of what emotional support can be about: Sharing the pain of life and recognizing the struggle of life. The essay shows what can be at stake in vulnerable situations between the one who needs emotional support and the one who emotional supports. These are critical moments where the choice of action will have an impact on whether the other person experiences being seen, recognized, and taken care of.